2019
DOI: 10.1002/jgt.22457
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow triangles and the Caccetta‐Häggkvist conjecture

Abstract: A famous conjecture of Caccetta and Häggkvist is that in a digraph on n vertices and minimum outdegree at least n/r there is a directed cycle of length r or less. We consider the following generalization: in an undirected graph on n vertices, any collection of n disjoint sets of edges, each of size at least n/r, has a rainbow cycle of length r or less. We focus on the case rgoodbreakinfix=3 and prove the existence of a rainbow triangle under somewhat stronger conditions than in the conjecture. In our main resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…. By (1) , the cycle matroid of G. We use the well-known fact that r N r N E G n ( ) + ( ) = | ( )| = 2 * . Therefore, since N has rank n N − 1, * has rank n + 1.…”
Section: Matroid Generalizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…. By (1) , the cycle matroid of G. We use the well-known fact that r N r N E G n ( ) + ( ) = | ( )| = 2 * . Therefore, since N has rank n N − 1, * has rank n + 1.…”
Section: Matroid Generalizationsmentioning
confidence: 99%
“…Given a graph G and a coloring c of E(G), we say that a subgraph H of G is rainbow if no two edges of H are of the same color. Aharoni (see [1]) recently proposed the following strengthening of the Caccetta‐Häggkvist conjecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming negation, for every v ∈ A there exists w ∈ V (D) such that N + (w) = {v}. The w-term in the right hand side of (1) is then 1 2 , while the left hand side is at most 1 2 , and thus for the inequality to hold necessarily N − (v) = {w} and deg + (v) = 1. Namely, both in-degree and out-degree of v are 1.…”
Section: Proof the Condition φ(Dmentioning
confidence: 99%
“…Hompe also showed that this is false for digraphs with maximal out-degree larger than 2. In his construction, g(D) > ψ(D) ln 2+o (1) . In this paper we prove:…”
Section: Introductionmentioning
confidence: 96%